2018
DOI: 10.3390/nu10081023
|View full text |Cite|
|
Sign up to set email alerts
|

A Low FODMAP Gluten-Free Diet Improves Functional Gastrointestinal Disorders and Overall Mental Health of Celiac Disease Patients: A Randomized Controlled Trial

Abstract: A subset of patients with celiac disease (CD) on a gluten-free diet (GFD) reported the persistence of functional gastrointestinal disorders. Foods containing fermentable, oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAP) can trigger a broad range of gastrointestinal symptoms in sensitive individuals. We evaluated the effects of a low FODMAP diet (LFD) on gastrointestinal and psychological symptomatology in CD patients. A total of 50 celiac patients on GFDs and with persistence of gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 35 publications
(42 reference statements)
4
54
0
3
Order By: Relevance
“…At the end of the 21 days, symptoms were reduced in the LF-GFD group, but not in the R-GFD group. General wellbeing increased in both groups, but a significantly higher improvement was noted in the LF-GFD group [26]. This suggests an additive effect of combining a low FODMAP diet with a GFD in certain individuals with NRCD.…”
Section: An Associated Conditionmentioning
confidence: 77%
See 1 more Smart Citation
“…At the end of the 21 days, symptoms were reduced in the LF-GFD group, but not in the R-GFD group. General wellbeing increased in both groups, but a significantly higher improvement was noted in the LF-GFD group [26]. This suggests an additive effect of combining a low FODMAP diet with a GFD in certain individuals with NRCD.…”
Section: An Associated Conditionmentioning
confidence: 77%
“…In addition, functional gastrointestinal disorders, such as irritable bowel syndrome (IBS) and gastrointestinal dysmotility, are more prevalent in individuals with CD [23,24] and should not be overlooked as a cause of persisting symptoms in individuals with normal repeat duodenal histology. For these individuals, a low fermentable oligo-, di-, mono-saccharide and polyol (FODMAP) diet may improve symptoms and quality of life [25,26]. In one study, 41 CD patients with IBS who had been on a GFD for at least 1 year demonstrated significant improvement in IBS-symptom severity scores after 3 months on the low FODMAP diet [25].…”
Section: An Associated Conditionmentioning
confidence: 99%
“…CD patients following a GFD consume inadequate fiber levels, especially women, with intakes of 13.7 g per day [ 15 ] and 12 g per day [ 14 ] observed in UK dietary studies (fiber expressed as non-starch polysaccharides). There is limited scientific evidence of the effects these products have on the digestive system, but recently a study has shown that a subset of CD patients is sensitive to fermentable fibers [ 22 ]. Understanding these effects is important, especially as the digestive mechanism of CD patients may differ to that of the general population, as CD is an abnormal immune response to a food component.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this increase include easier diagnostic methods and better targeted screening [4,5]. In addition to classic gastrointestinal (GI) symptoms, extra-intestinal symptoms such as neurological, psychiatric, and skin related are increasingly recognised [1,[6][7][8][9]. These extra-intestinal symptoms when presenting in isolation are challenging in the diagnosis of CD [1,10].…”
Section: Introductionmentioning
confidence: 99%